FRI0203 Pulmonary involvement in juvenile scleroderma. (1st June 2001) - Romicka, AM; Malinowski, A
Abstract : Background: Scleroderma in children manifests more frequently in the form of localised disease than syptemic one. This disorder is characterised by the presence of hard and tight skin (linear, localised and generalised morphea); systemic sclerosis, besides the skin changes it manifests the internal organ involvement. Objectives: The aim of this report was an assessment of the frequency and nature of lung lesions in children with scleroderma. Methods: The study comprised 32 non selected pts, aged from 4 to 18 yrs., 16 suffering from localised and 16 from systemic scleroderma. The disease duration ranged from 6 months to 14 yrs. The relation between clinical symptoms, x – ray findings and functional pulmonary tests were performed. Results: Clinical and/or radiological signs (cought, dyspnoe, interstitial thickening) were found in 9 pts. The results of the functional investigation showed an impairment of the pulmonary function in 80.6% of pts with systemic sclerosis and 50% – with localised scleroderma, (total 65.6%). A decrease in DLCO (in 1/3 of pts in association with restrictive ventilatory failure) belonged to the most frequent of the lung damages. Conclusion: Pulmonary involvement is frequent, however not a main feature in the course juvenile scleroderma. Abnormalities in functional tests were often the only manifestation of the respiratory sys-tem involvement. Lung functional disturbances may be independent of clinical features, muscular on skin involvement. Respiratory functional tests are helpful in estimation of systemic scleroderma in the cases manifesting only the clinical form of localised one. References: Chomette G, Tranbaloc P, Beaufils H, et al . Les sclerodermies viscerales. Ann Med Interne (Paris) 1984;135:606 Greenwald GI, Tashkin DP, Gong H, et al . Longitudinal changes in lung function and respiratory symptoms in progressive systemic sclerosis. Am J Med. 1987;83:83 Lahman TJA. Systemic and localized scleroderma in children. Curr Opin Rheumatol. 1995;8:576 Uziel Y, Miller H, Lazar RM. Scleroderma in children. Pediatr Clin North Am. 1995;42:1171 Deheu I, Roujcan J-C, Cosnes A. Revuz: internal involvement in localized scleroderma. Medicine (Baltimore) 1994;73:241 Laxer RM, Feldman BM. General and local scleroderma in children and dermatomyositis and associated syndromes. Curr Opin Rheumatol. 1997;9:458